Local vs. Avatar Robot: Performance and Perceived Workload of Service Encounters in Public Space - Baba, Jun; Song, Sichao; Nakanishi, Junya; Yoshikawa, Yuichiro; Ishiguro, Hiroshi (Frontiers in Robotics and AI, 2021)
In recent years, the demand for remote services has increased with concerns regarding the spread of infectious diseases and employees’ quality of life. Many attempts have been made to enable store staff to provide various services remotely via avatars displayed to on-site customers. However, the workload required on the part of service staff by the emerging new work style of operating avatar robots remains a concern. No study has compared the performance and perceived workload of the same staff working locally versus remotely via an avatar. In this study, we conducted an experiment to identify differences between the performance of in-person services and remote work through an avatar robot in an actual public space. The results showed that there were significant differences in the partial performance between working via an avatar and working locally, and we could not find significant difference in the overall performance. On the other hand, the perceived workload was significantly lower when the avatar robot was used. We also found that customers reacted differently to the robots and to the in-person participants. In addition, the workload perceived by operators in the robotic task was correlated with their personality and experience. To the best of our knowledge, this study is the first investigation of both performance and workload in remote customer service through robotic avatars, and it has important implications for the implementation of avatar robots in service settings.